The study on quality of catfish (pangasius hypopthalmus) Nugget added with carrot (daucus carota l.) - Nelda wati; Dahlia '; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
types of nugget were made from a mixture of catfish meat (50%), tapioca flour (15%) andspices (11,6%). The mixture then was added with carrot flour at a level of 0%, 5%, 10% and 15%.The nugget was evaluated for sensory quality, moisture, protein, fat, fiber, ash and bacterial caunt.The result showed that the catfish nugget added with 10% carrot flour was the best in quality.Moisture, protein, fat, fiber, ash and bacterial caunt of the nugget was (58,03%), (8,21%), (9,61%),(12,11%), (3,31%) and 31,34 x 103 respectively.Keywords: catfish, carrot flour, nugget.